Penerapan Model Pembelajaran Project Based Learning (PjBL) melalui Pendekatan Diferensiasi terhadap Peningkatan Kreativitas dan Hasil Belajar Peserta Didik dalam Materi Sistem Koordinasi di Kelas XI SMA Negeri 13 Samarinda - Lestari, Endah Puji; Maasawet, Elsje Theodora; Lumowa, Sonja Verra Tinneke; Makkadafi, Suparno Putera; Rambitan, Vandalita Maria Magdalena (Biocaster : Jurnal Kajian Biologi, 2025)
This study aims to determine the effect of the implementation of the Project Based Learning (PjBL) learning model through a differentiation approach in improving creativity and learning outcomes of students in class XI of SMA Negeri 13 Samarinda. This research method uses a quantitative approach with a non-equivalent control group design. The population in this study was all class XI of SMA Negeri 13 Samarinda. Sampling used a purposive sampling technique. The sample in this study was class XI Moving Biology (XI-5 and XI-8) as an experimental class using the Project Based Learning (PjBL) learning model through a differentiation approach and XI-3 as a control class using a conventional learning model. Data were collected through tests in the form of essay questions and observation sheets. The data from the test questions and observation sheets were analyzed using an independent sample t-test and an N-gain test with the help of a data processing application. The statistical test results obtained from the independent sample t-test on creativity showed a significance value of 0.000 < 0.05, as well as the independent sample t-test on learning outcomes of 0.011 < 0.05, so H0 was rejected and Ha was accepted. It can be concluded that there is an influence of the application of the Project Based Learning (PjBL) learning model through a differentiation approach on creativity and learning outcomes of students in the experimental class. Furthermore, the N-gain test showed an increase in student learning outcomes after implementing the Project-Based Learning (PjBL) model through a differentiation approach, with an N-gain score of 0.91, in the high category. These research results indicate that implementing PjBL with a differentiation approach can be an effective alternative learning strategy for developing creativity and improving student learning outcomes in high school.